2008
DOI: 10.1016/j.cpr.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual coercion and the misperception of sexual intent

Abstract: Misperceiving a woman's platonic interest as sexual interest has been implicated in a sexual bargaining process that leads to sexual coercion. This paper provides a comprehensive review of sexual misperception, including gender differences in perception of women's sexual intent, the relationship between sexual coercion and misperception, and situational factors that increase the risk that sexual misperception will occur. Compared to women, men consistently perceive a greater degree of sexual intent in women's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
131
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 89 publications
11
131
1
5
Order By: Relevance
“…It is possible, for example, that increased sexual objectification, brought on by myopia, may be an underlying process that contributes to outcomes such as men's misperceptions of women's sexual interest and related sexual aggression (Abbey et al 2000). If men who are under the influence of alcohol pay less attention to the humanizing attributes of women (e.g., through decreased focus on facial cues), they may be less able to gauge women's sexual interests accurately (Farris et al 2008). Furthermore, for women who are targets of objectification, these experiences may potentially act as a precursor to behavioral confirmation in which women begin to self-objectify (Kozee et al 2007), leading to safety concerns (Fairchild and Rudman 2008), negative affect, reduced flow, increased body monitoring, and shame (Calogero et al 2011;Noll and Fredrickson 1998;Tiggemann and Williams 2012).…”
Section: Practice Implicationsmentioning
confidence: 99%
“…It is possible, for example, that increased sexual objectification, brought on by myopia, may be an underlying process that contributes to outcomes such as men's misperceptions of women's sexual interest and related sexual aggression (Abbey et al 2000). If men who are under the influence of alcohol pay less attention to the humanizing attributes of women (e.g., through decreased focus on facial cues), they may be less able to gauge women's sexual interests accurately (Farris et al 2008). Furthermore, for women who are targets of objectification, these experiences may potentially act as a precursor to behavioral confirmation in which women begin to self-objectify (Kozee et al 2007), leading to safety concerns (Fairchild and Rudman 2008), negative affect, reduced flow, increased body monitoring, and shame (Calogero et al 2011;Noll and Fredrickson 1998;Tiggemann and Williams 2012).…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Similarly, a review study (18) showed that compared with women, men consistently perceived a greater degree of sexual intent in women ' s behavior. Misperception has been shown to be often constructed after an assault for the perpetrator to absolve himself of guilt (19) .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, in comparison to women, men more likely frame their opposite-sex interactions using a socialsexual relational schema and women interpret relational schemas as friendship (Farris, Treat, Viken, & McFall, 2008b;LaFrance, Henningsen, Oates, & Shaw, 2009;Lindgren, Parkhill, George, & Hendershot, 2008). Men presented with ambiguous cues such as touching and prolonged eye contact are more likely than are women to assume sexual intent and to rate female targets as sexy, promiscuous, and seductive (Abbey & Melby, 1986).…”
Section: Female Interests Are Misperceived By Men (Gender Differencesmentioning
confidence: 99%